Sociodemographic and clinical correlates of human papillomavirus vaccine attitudes and receipt among Wisconsin adolescents - Kayla E. Hanson; Huong Q. McLean; Edward A. Belongia; Shannon Stokley; Michael M. McNeil; Julianne Gee; Jeffrey J. VanWormer (Papillomavirus Research, 2019)
Few studies have assessed adolescent human papillomavirus (HPV) vaccine attitudes and whether they are associated with vaccination uptake. This study characterized HPV vaccine attitudes among male and female adolescents, identified factors associated with attitude changes, and examined associations between attitudes and vaccination receipt. Surveys were administered to adolescents aged 15–16 years who had not completed the HPV vaccine series. A modified version of the Carolina HPV Immunization Attitudes and Beliefs Scale (CHIAS) was employed to assess barriers, harms, ineffectiveness, and uncertainties scores. Surveys were available from 108 participants; 63% were male and 33% had initiated the HPV vaccine series at baseline. CHIAS scores significantly decreased (i.e., became more favorable) between baseline and follow-up for barriers (p = 0.01) and uncertainties (p < 0.01). At least one sociodemographic/clinical factor was associated with changes in each score. Attitude changes were not associated with receipt of HPV vaccine, although adolescents with higher baseline harms scores were significantly less likely to receive an HPV vaccine dose (OR = 0.67). Adolescents’ HPV vaccine attitudes slightly improved over a one-year period during which an intervention was implemented. More research is needed to learn how parent and adolescent HPV vaccine attitudes form, and how best to address concerns about vaccine harms. Keywords: Human papillomavirus, Vaccination, Adolescents, Attitudes, Harms, Epidemiology